Integrating Facebook as a Web 2.0 tool in a responsive pedagogy for multimodal oral presentation skills - Lee, Sze Seau; Hazita Azman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Technology both complicates and liberates oral presentation pedagogy in higher education. On one hand, 21st century communication realities require students to deliver multimodal oral presentations but educators have only begun to experiment with the relevant pedagogy. On the other hand, Web 2.0 offers vast pedagogical potential which practitioners have just begun to explore. Confronted by a pedagogical predicament and intrigued by the affordances of Web 2.0, we designed the Responsive Multimodal Oral Presentation Pedagogy (RMO2P) to enhance the learning of multimodal oral presentation skills among EAP (English for Academic Purposes) students. RMO2P integrated Facebook as a Web 2.0 tool with videos, collaborative learning and feedback. A teacher-researcher implemented RMO2P in a public speaking class of 20 EAP students for a semester. Thematic analysis of multiple sources of data which included student artifacts, observational data and inquiry data contributed to the findings. The findings indicated that Facebook was a feasible Web 2.0 tool that can be effectively integrated with other pedagogical techniques. As a result, the participants demonstrated enhanced conceptual knowledge and heightened self-awareness as presenters of multimodal oral presentations. Since Facebook was integrated as a Web 2.0 tool in a responsive method for multimodal oral presentation skills to overcome situational constraints including inadequate learning management systems (LMS), stakeholders who are seeking alternative methods to enhance the teaching of oral presentation skills may adapt the intervention to enhance learning outcomes.